(untitled) (Research, Society and Development, 2022)
Introduction: Female sexual dysfunction occurs when a woman is unable to achieve or has any disorder related to sexual desire, excitability, orgasm or sexual pain. Anorgasmia is a clinical situation that affects mainly women and has its origins in several causes, which may be related to trauma, physical or physiological changes. In recent years there has been a higher incidence of women with sexual dysfunctions, and in this context, physiotherapy appears as an advance related to treatment and the main effective alternative for women who have these dysfunctions. Objective: To provide the scientific basis to support the best physiotherapeutic treatments for women with anorgasmia, since the physiotherapeutic techniques used are relatively recent in the treatment of women with this dysfunction. Methodology: This is a bibliographic survey on the role of physiotherapy in the treatment of female sexual dysfunction. Final considerations: Treatment for women happens with or without partners. The act of "touching", getting to know your body and understanding how everything works is already part of the treatment, and the support of the partner and psychological follow-up brings more courage for women to face this moment. Currently there are several physiotherapeutic techniques that promote the improvement of sexual dysfunctions, they must be combined with the awareness of women and their partners. In addition, physical therapists must have a scientific basis in the approach to treatment and remain in constant updates, demonstrating the effectiveness of treatments and responsibility in the adequacy of therapies instituted according to the main complaints reported by each woman.